Leakage-Resilient Certificate-Based Signature Resistant to Side-Channel Attacks - Wu, Jui-Di; Tseng, Yuh-Min; Huang, Sen-Shan; Tsai, Tung-Tso (IEEE access, 2019)
Certificate-based cryptography is an attractive public-key setting, and it not only simplifies certificate management in the traditional public-key cryptography but also eliminates the key escrow problem inherent in the identity-based cryptography. Recently, leakage-resilient cryptography resistant to side-channel attacks has received significant attention from cryptographic researchers. By side-channel attacks, adversaries could obtain partial information of secret and private keys involved in cryptographic algorithms by perceiving execution time or energy consumptions of each algorithm invocation. The certificate-based signature (CBS) is a class of important public-key signature. Up to date, there exists no leakage-resilient CBS (LR-CBS) scheme resistant to side-channel attacks. In this paper, the first LR-CBS scheme is proposed and it possesses overall unbounded leakage property, namely, it permits adversaries to continuously obtain partial information of secret or private keys involved in the associated algorithm invocations. The security analysis is given to prove that the proposed LR-CBS scheme is existential unforgeability against adaptive chosen-message attacks for adversaries in the generic bilinear group model.